Conquering the experiences of pain, boredom and despair among selected incarcerated mothers through alternative learning system activities - Rowena Vargas Isidro; Roberto Oberio; John Paul Javero Petrola (International Journal of Public Health Science (IJPHS), 2022)
This paper aims to describe the life stories and experiences of mothers in prison who have overcome their pain, boredom, and despair through the learning and recreational activities, as part of the alternative learning delivery. Analysis was done using Arthur Schopenhauer’s lens. This is grounded on the idea that incarcerated mothers have experienced what Schopenhauer described as sufferings of the world which comprises the inevitable feelings of pain, boredom and despair in their entire stay at the four corners of prison cells. In this paper, face-to-face interviews, phone conversations and critical analysis in the appropriation of Schopenhauer’s pessimistic concepts were employed. As a result, three themes were drawn, namely, winning over emotional and psychological anxieties, seeing the silver lining, and determination to freedom. This paper recommends to the department of education (DepEd), commission on higher education (CHED) and technical education and skills development authority (TESDA) to further extend their community services or extension function for the continuation and enhancements of the delivery of alternative learning system (ALS) among incarcerated Filipino mothers, which the society is referred to as ilaw ng tahanan (light of every home).